A photolithography tailored undulating configuration to confine nanostructures on microtubes via a "stress-induced" effect for boosting sodium ion storage. Issue 36 (1st September 2022) - Shi, Haiting; Zhang, Xinyi; Min, Chunying; Xia, Yuanhua; Liang, Shuaitong; Liu, Shengkai; Liu, Liangsen; Wang, Wei; Xu, Zhiwei; Cai, Zhijiang
Abstract : Undulating structure and internal graphite lattice distorted structure were induced via high-penetrating gamma irradiation. A stress-inducing strategy is supplied to obtain electrode materials. Advanced characterization was used to assess the structural evolution. Abstract : The lack of a suitable stress dispersion structure to avoid the mechanical deformation of the material when constructing anode materials for sodium-ion batteries (SIBs) greatly hinders sodium storage behavior. Here, high-penetration gamma irradiation induces an undulating configuration in kapok fibers, where self-assembled molybdenum disulfide (MoS2 ) is anchored. Synchrotron radiation techniques, nanoindentation, density functional theory (DFT) calculations, and finite element simulations were conducted to evaluate the structural evolution of the fibers after gamma irradiation, the nucleation growth of MoS2, and the contact stresses between them. We proved that the undulating configuration not only facilitates the homogeneous nucleation, growth, and domain-limited anchoring of MoS2, thereby adequately limiting volume expansion, but also effectively ameliorates the stress concentration phenomenon in the overall section. This work shows a counter-intuitive mechanism whereby the undulating configuration with high curvature resulting from gamma irradiation contributes to the excellent mechanical properties in the aggregation of nanomaterials.